Initial performance of Malaysia Shariah-compliant IPOs - Nor Azizan Che Embi; Ruzita Abdul Rahim; Izani Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
This book is a response to the development in the Malaysian IPO market which in 2004 witnesses the introduction of pre-IPO Shariah status.